A Rapidly Modulated Multifocal Detection Scheme for Parallel Acquisition of Raman Spectra from a 2‑D Focal Array - Kong, Lingbo; Chan, James (Analytical chemistry (Washington), 2014)
We report the development of a rapidly modulated multifocal detection scheme that enables full Raman spectra (∼500–2000 cm–1) from a 2-D focal array to be acquired simultaneously. A spatial light modulator splits a laser beam to generate an m × n multifocal array. Raman signals generated within each focus are projected simultaneously into a spectrometer and imaged onto a TE-cooled CCD camera. A shuttering system using different masks is constructed to collect the superimposed Raman spectra of different multifocal patterns. The individual Raman spectrum from each focus is then retrieved from the superimposed spectra with no crosstalk using a postacquisition data processing algorithm. This system is expected to significantly improve the speed of current Raman-based instruments such as laser tweezers Raman spectroscopy and hyperspectral Raman imaging.